IT-ITES trade of SAARC countries: does kaleidoscopic comparative advantage work?. (2016) - Bharti, Nalin; Gaurav, Kumar; Kumar, Chandan
Though, liberalisation of services trade is a new phenomenon, it has witnessed sustained growth and acceptance in recent decades. IT/ITES and its trade became the fastest growing sub-sector of trade in services. Services trade of SAARC countries became more dynamic in the post Uruguay Round. These economies are more integrated with the other economies of the world in services. Volatile comparative advantage with knife-edge specialisation pioneered the phrase, kaleidoscopic comparative advantage applicable equally to trade in services. In this backdrop, this study applied the qualitative (analysis of IT and telecommunications policy of all the SAARC countries) as well as quantitative methods (revealed comparative advantage - RCA index and services trade openness has been calculated) to capture the potentialities and competitiveness of IT/ITES trade of SAARC. This paper argues that the kaleidoscopic comparative advantage is not fixed only to bigger economies like India, but it has also extended to comparatively smaller economies like Sri Lanka, Bangladesh, and Pakistan.